Cebu School of Arts and Trades and a follow-up study of its five hundred forty graduates - Abad, Rosario V. 1918- (1955)
Attempts on determining the role the Cebu School of Arts and Trades plays in developing vocational competency among the people in Eastern Visayas, Mindanao and Sulu was represented in this study. The study is especially directed to the follow-up of graduates of the school.